Territórios, multiterritorialidades e memórias dos povos Guarani e Kaiowá: diferenças geográficas e as lutas pela Des-colonização na Reserva Indígena e nos acampamentos-tekoha - Dourados/MS - Mota, Juliana Grasiéli Bueno [UNESP] (2015)
The central objective of this study is to describe and explain the geographical differences between the Indian Reservation and encampments-tekoha that have recently been established in the municipality of Dourados in the state of Mato Grosso do Sul, Brazil. Through a conceptual approach to territory, the study dialogues with the categories of native Guarani and Kaiowá people, with tekoha and tekoha guasu - native terms that denote the periods before and after the dis/encounter with the karaí - the white. The concept of decolonization is used to analyze the lingering impact of colonialism on interethnic relations in both these spaces. Founded in 1917 by Brazil's Indian Protection Service, the reserve long operated under a policy of assimilation through civilization. In the last several years, indigenous people have fought to create their own territories, initially in the form of land occupations - in nearby camps, variously denominated as tekoha Apika'y, Pacurity, Ñu Porã, Ñu Verã and Boqueron. While the reserve consolidates colonialism, the tekoha geographically represent the struggle for decolonization taking place today in actions meant to recover ancestral territories. The tekoha movement expresses a rebellion against colonial reserve status, as well as the agrarian capitalism paradigm that predetermines rural land usage for crops rather than communities. We argue that the geographical differences between these territories arise not only from the material differences of the two spaces, but above all from complex immaterial differences. These include differences in perceptions of processes of geographical des/repossession - the multi-territoriality - of territorial construction and destruction, on the connections and disconnections...